Rodinný dům - Šefflová, Magdaléna (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Jedná se o novostavbu rodinného domu. Objekt má dvě nadzemní a jedno podzemní podlaží. Rodinný dům bude sloužit k trvalému bydlení 4 osob. Obvodové nosné stěny jsou navrženy jako monolitické železobetonové, z tepelně – izolačního betonu Liaver. Stropní konstrukce je železobetonová jednostranně vyztužená deska, střecha je plochá jednoplášťová. Obvodové stěny jsou provedeny z pohledového betonu nebo obloženy obkladem z přírodní břidlice.

This is a construction of a new family house. Building has two floors above ground and one below ground. This family house will be a permanent home for four people. Perimeter load-bearing walls are designed as monolithic and reinforced concrete walls made from thermal insulating concrete Liaver. Ceiling construction is made from reinforced concrete and one-sided reinforced plate and roof is flat and single-layered. Perimeter walls are made from exposed concrete or paneled with natural slate.
Family House
Keywords: Tepelně – izolační beton; Pohledový beton; Jednoplášťová plochá střecha; Železobeton; Thermal insulating concrete; Exposed concrete; Single-layer flat roof; Reinforced concrete